Power Girl : power trip - Gray, Justin (Comic book writer); Palmiotti, Jimmy; Johns, Geoff, 1973-; Conner, Amanda (DC Comics, 2014)
"Power Girl is making a fresh start. She's left behind her old life--and old Earth--to reinvent herself in New York City. As Karen Starr,she's running the newly reopened Starrware Labs,one of the most innovative tech companies on Earth,and as Power Girl,she's on her way to becoming the Big Apple's favourite super hero. But is she making her new home a target? The human-brain/ape-body entity known as the Ultra-Humanite and his followers have a plan to take control of Power Girl's super-human body. She, however, won't let herself be brain-swapped without a fight. But as Power Girl battles through the skies and the streets to save her bulletproof skin, all of New York City could end up becoming collateral damage!"--page [4] of cover.